DIGITAL IMAGE WATERMARKING OF COMPRESSED IMAGE USING JPEG2000 AND ENCRYPTION TECHNIQUES - Bhagyashri D. Shende; Prof. Mrs. R. J. Shelke (International Journal of Innovations in Engineering Research and Technology, 2021)
The necessity for copyright protection, ownership verification, and other issues for digital data are getting more and more value these days. For the rapid revolution in digital multimedia and the ease ofcreating similar and unauthorized data, the digital data can be copied or manipulated or distributed. So it is necessary to watermark the media content for tamper proofing or quality assessment or copy control. In this paper we propose a JPEG2000 compression. The compression standard is chosen such that it provides higher compression ratio and the compressed byte stream are randomized by the encryption algorithm. In our paper watermarking was done in the compressed – encrypted domain. We use different watermarking techniques for this. Attempting to watermark such a randomized bit stream can cause a dramatic degradation of the media quality.